Assembleias e Padrões Alimentares de Peixes da Reserva Biológica do Córrego Grande, Conceição da Barra, Espírito Santo, Brasil - Ribeiro, Marcella Bueno (2020)
The present study was developed with the objective of investigating the food trophic structure of stream fishes in relation to temporal seasonality (dry and rainy seasons) in the Itaúnas River Basin, within the scope of the Córrego Grand